Need or Greed: Young Peopleâs Financial Support Expectations and Cross-Cultural Differences - Maadad, Nina (SOSIOHUMANIKA, 2012)
ABSTRACT: Most parents, teachers, and guardians understand that children, no matter what their age, have needs for certain things in life to help them develop physically, emotionally, and mentally. There are many things that children themselves want. In our daily lives a âneedâ or a âwantâ may sound very similar, so that differentiation between the two is not always clear. This paper explores the distinction between needs and wants and the different ways and means young people use to achieve these ends in Western society. It also looks at how parents react and deal with their children when the expectations rise and their needs and wants become more expensive. Sixty students, all aged between 16 and 22 years old, filled in questionnaires. They were from four different school sectors, five different cultural backgrounds, and two universities in South Australia. Twenty were later interviewed to document their experiences and stories. Data was analysed qualitatively for factors affecting attitude, lifestyle, core values, culture, and their impact on the behaviour outcomes. The study further examined how these patterns of behaviour reflected on the studentsâ life skills, achievements, and how they affected family outcomes. Results showed that many parents took the blame for their childrenâs actions and illustrated the influence of values and cultural background on childrenâs attitude towards their parents, their needs, and expectations.Key words: Young people, diversity in cultural upbringing, psychological experiences, lifestyle expectations, and increasing demands of children and culture.About the Author: Dr. Nina Maadad is Associate Head Learning and Teaching BTeach Coordinator at the School of Education, University of Adelaide, 8/10 Pultney Street, Adelaide, Australia. For academic purposes, she can be reached at: nina.maadad@adelaide.edu.auHow to cite this article? Maadad, Nina. (2012). âNeed or Greed: Young Peopleâs Financial Support Expectations and Cross-Cultural Differencesâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.1 [Mei], pp.1-20. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 11, 2012); Revised (April 13, 2012); and Published (May 20, 2012). Â  Â